Low-temperature impairment of erythrocyte membrane barrier properties – a result of the disorganization of the supramolecular hemoglobin structure - Gulevsky, A.K.; Repin, M.V.; Schenyavsky, I. I. (Reports of the National Academy of Sciences of Ukraine, 2015)
Cryoresistances of native erythrocytes and resealed erythrocyte ghosts are compared. It is found that resealed erythrocyte ghosts, where the hemoglobin content is 4–5 times lower than that in erythrocytes, and it is in the form of a molecular solution, are much more cryoresistant than native erythrocytes, which is especially noticeable, when a low concentration of the cryoprotectant (4% glycerol) is used. These data confirm the earlier proposed hypothesis about the role of the supramolecular hemoglobin structure in the mechanism of cryoinjury of erythrocytes.